ABSORBTION EFFICIENCY OF IPARD FUNDS IN FINANCING MACEDONIAN AGRITOURISM DEVELOPMENT - Ackovska, Marija; Petrovska-Angelovska, Neda; Hadzi Naumova-Mihajlovska, Katerina (International Balkan and near eastern social sciences conference series (IBANESS), 2016)
In this paper is elaborated the availability of IPARD funds enabling opportunities in supporting the countries toward EU accession. A special focus is paid to their efficiency in financing development of agritourism in the Republic of Macedonia. The paper concludes that the EU funds offer a great opportunity for rural tourism development, but its absorption is very low. Namely through IPARD funds are offered good opportunities for developing the agritourism in Macedonia. Unfortunately, these funds are not satisfactory used and the reasons for the low absorption level are manifold. One of the reasons is the lack of coordination across national and local institutions, relatively low awareness of citizens and organizations for the opportunity offered by IPARD and difficulties related to the criteria that applicant have to fulfill for absorption of funds for different measures. For that purpose, desk research is conducted as well as the inputs of different stakeholders dealing with the field of agritourism.
Keywords: Agritourism; IPARD; efficiency, development; Republic of Macedonia